Histological study of the developing gonads of endangered freshwater spiny eel, Mastacembelus armatus during the reproductive cycle - Ali, MR; Rahman, MM; Sarder, MRI; Mollah, MFA (Journal of the Bangladesh Agricultural University, 2017)
The spiny eel, Mastacembelus armatus is one of the most common and economically important inland teleost species of Asia having high market and nutritive values. The demand for the fish is almost always exceeds its supply. Histological analysis of developmental stages of both oocytes and sperrnatocytes maturation were undertaken and dimensions of ovarian oocytes were observed to evaluate the annual reproductive condition of M. armatus during August 2012 to July 2013. Monthly sampling of adult individuals of M. armatus was done from haor region of Kishoreganj district, Bangladesh. Both the gonads were paired, elongated and of unequal in length. The colour of ovaries varied from reddish brown to light yellowish; whereas, testes varied from whitish to creamy or dull white. From the histological study, five stages of oocyte development (oogonia, chromatin nucleolar stage oocyte, perinucleolar stage oocytes, yolk vesicle oocyte, and yolk granule stage) were observed upon their changes in nucleus. Female M. armatus having immature stages of oocytes (early and late perinucleolar stage oocytes) were mostly available in the months of November and December. Yolk vesicle stage oocytes appeared during the months of January and February. Early yolk granule stage oocytes appeared during the months of March and April while late yolk granule stage oocytes were observed during the months of May and June. Oocytes and nuclei diameters were observed ranged from 121050 ?m and 10212 ?m, respectively until ovulation. In male gonads, four stages of spermatogenesis (spermatogonia, spermatocytes, spermatids, and spermatozoa) were distinguished during the study period where spermatids were prominent in January to March and spermatozoa in April to July. From this study, the peak gonadal development of M. armatus is found in June and thus, it is clearly indicated that the fish breed during May to June. J. Bangladesh Agril. Univ. 14(2): 261-269, December 2016